A systemic overview of football game: The principles behind the game - Clemente, F. M.; Lourenco Martins, F. M.; Sousa Mendes, R.; Figueiredo, A. J. (Journal of Human Sport & Exercise, 2014)
The football game is a specific systemconstituted by many players` interactions. The specific nature of such sportmust be properly analyzed and discussed in sport community in order tounderstand the principles that rules the system organization. As a team sportwith specific properties it is truly important to discuss how players`interactions from the dynamic nature of game. Therefore, the aim of this studyis to classify the football game as a team sport and to discuss their specificdynamic that determines the emergence of a tactical behavior and a strategicdefinition. Such discussion can be important to determine the specificpedagogical and didactical contents to teach at youth football training andeven in Physical Education classes.